Educate citizens through take action on community problems (Praxis Educativa, 2020)
The way in which people think about democracy determines their chances to influence society. Therefore, one the most important aims of citizenship education is the students' understanding of all forms of democratic participation. This article presents the results of an action research study which has sought to influence the ideas of citizen participation in a group of Chilean high school students. To do this, a didactic sequence called "Action on Social Problems Module" was designed and implemented. Data was collected using a mixed method approach, therefore questionnaires, interviews, focus groups, video recordings and field notes were implemented. The young people's ideas were classified by a reformulation of the categories that McLaughlin has previously used to describe the notions of citizenship. It was determined that the didactic proposal was effective to expand the conception of citizen participation of the students involved and improvements were established for their future applications.
Keywords: citizenship education; citizen participation; social problems; social representations; controversial issues.